FUNCTIONAL APPROACHES TO RED TOURISM: STANDARDIZING ENGLISH TRANSLATION FOR GLOBAL AUDIENCES - Ying, Zhang Xiu; Dao, Liu Hong (Research Journal of Education and Allied Studies, 2024)
China's rapidly growing tourism industry, driven by its expanding engagement with the world, is increasingly making use of English materials to facilitate tourist access to its remarkable "Red tourism" resources. Red tourism, as a novel form of tourism, embodies unique allure and profound cultural significance. Hence, it is paramount to address the existing challenges in the English translation of Red tourism materials. Functional theory, a contemporary approach to text translation, underscores the purposive and systematic nature of translation. In recent years, functionalism has been successfully applied across diverse domains in China. As a pivotal facet of cultural exchange, English translation in Red tourism aims to introduce China's rich "Red culture" to international tourists. In line with functionalist principles, this paper underscores the need for text and reader analysis when confronting translation issues, placing the translator at the heart of the translation process. Considering the paramount importance of English translation for Red tourism in China, this paper advocates standardized strategies to enhance the quality and proficiency of Red tourism translation efforts.